https://www.journal-imab-bg.org/issues-2025/issue2/vol31issue2p6207-6211.html - Gergana Gecheva-Fermendzhieva (Journal of IMAB)
It is presented in this study a case of 54 years old man with stroke and chronic right hemiparesis and Wernicke-Mann gait hospitalized in the medical center for rehabilitation with kinesiotherapy and botulinum toxin injection. Six months ago, he got an acute headache, tingling in the right hand, inability to move the right lower and upper limb, as well as inability to walk independently. Hospitalized in the Neurology department, where an MRI of the brain was conducted and exhibited hemorrhagic stroke. The patient complained about instability of the right leg and difficulty in daily activities. Observational gait analysis showed violations in flexion of the right knee due to spasticity of m.quadriceps femoris dextra during the stance phase of the gate. Dynamic smart insoles recordings showed increasing in knee flexion and gait velocity after botulinum toxin injection in parallel with systematic kinesiotherapy, which lasted 1 month. The results exhibited that spastic gate disorders can improve with systemic kinesiotherapy and spasticity-reducing agents such as botulinum toxin A.